The market perception of corporate claims - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2003)
This paper examines the economic substance of a broad range of securities by investigating their association with systematic risk and prices. The analysis is motivated by continuing security innovation and its impact on hybrid security reporting. Based on a sample of 2,617 firms that reported minority interests or preferred stock during 1993–1997, the results indicate that redeemable preferred securities (including trust preferred stock) are not viewed by the market as either debt or equity, suggesting dichotomous security classification may lack representational faithfulness. Inconsistent with their treatment in the financial statements, non-redeemable preferred stock and minority interests are viewed as debt-like and equity-like respectively. Additional analyses document that the systematic risk and pricing results vary based on firm size, performance, and bond rating.